1995
DOI: 10.1002/j.1460-2075.1995.tb07220.x
|View full text |Cite
|
Sign up to set email alerts
|

A tyrosine-containing motif mediates ER retention of CD3-epsilon and adopts a helix-turn structure.

Abstract: Aut6noma de Madrid, Cantoblanco Madfid 28049 and 'Instituto de Estructura de la Materia, CSIC, Serrano 119, Madrid 28006, Spain 2Corresponding author Communicated by H.R.B.PelhamThe CD3-r endoplasmic reticulum (ER) retention motif has been characterized by mutagenesis and NMR spectroscopy. Iyr177, Leul80 and Argl83 are involved in ER retention. The motif forms an elongated a-helix in which the tyrosine and leucine residues are closely apposed, followed by a PI' turn that places Argl83 in the vicinity of Leul80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 61 publications
1
60
0
Order By: Relevance
“…While there are well-known examples of retrieval signals (Nilsson & Warren, 1994;Nilsson et al, 1989;Pelham, 1988), only a few true (static) retention motifs have been identified (Cocquerel et al, 1998(Cocquerel et al, , 1999. The fact that NSP4 does not contain the established ER retrieval-retention signal for type 1 transmembrane proteins -two lysines at 23 and 24 or 25 position (Jackson et al, 1993) or a tyrosinebased signal motif (Mallabiabarrena et al, 1995) -could indicate that NSP4 may contain a motif for a 'static retention signal' or an as yet unknown retrieval signal. Taylor et al (1996) have shown that cytoplasmic tail of NSP4 not only binds to microtubules but also inhibits anterograde protein trafficking, as illustrated by the inhibition of transport of VSV-G protein to the plasma membrane (Xu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are well-known examples of retrieval signals (Nilsson & Warren, 1994;Nilsson et al, 1989;Pelham, 1988), only a few true (static) retention motifs have been identified (Cocquerel et al, 1998(Cocquerel et al, , 1999. The fact that NSP4 does not contain the established ER retrieval-retention signal for type 1 transmembrane proteins -two lysines at 23 and 24 or 25 position (Jackson et al, 1993) or a tyrosinebased signal motif (Mallabiabarrena et al, 1995) -could indicate that NSP4 may contain a motif for a 'static retention signal' or an as yet unknown retrieval signal. Taylor et al (1996) have shown that cytoplasmic tail of NSP4 not only binds to microtubules but also inhibits anterograde protein trafficking, as illustrated by the inhibition of transport of VSV-G protein to the plasma membrane (Xu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Three sorting signals associated with ER retention and retrieval (Jackson et al, 1993;Lewis & Pelham, 1992;Pelham, 1994;Townsley & Pelham, 1994) have been proposed: (i) soluble proteins in the ER lumen carry a specific C terminus tetrapeptide retention signal, H/KDEL (Munro & Pelham, 1987); (ii) transmembrane proteins (type II) carry two arginines near the cytoplasmic N terminus (Schutze et al, 1994); and (iii) transmembrane proteins (type I) possess lysines at positions 23 and either 24 or 25 (Jackson et al, 1990). A tyrosine-based motif close to the C terminus has also been identified as an ER retention signal (Mallabiabarrena et al, 1995), but the retention mechanism for this motif is not yet known. In addition to such retrieval mechanisms, retention in the ER may also be static for glycoproteins that do not contain any of the above signal motifs (Cocquerel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The T-cell receptor delta chain displays a GYYYYV sequence in its membranous segment (33). That a tyrosine-containing motif mediates ER retention of CD3-⑀ chain has also been reported (34). To determine the topogenic importance of the tyrosyl residue cluster GFP chimera, Construct d lacking the tyrosyl residues in region II was generated.…”
Section: Fig 3 Electron Microscopic Immunogold Labeling Of Rab E3 Nmentioning
confidence: 99%
“…As a control, a truncated mutant of CD8␣ lacking the cytoplasmic tail was used (CD8t). Although the CD8/⑀ construct is in part retained in the ER because the cytoplasmic tail of CD3⑀ contains an ER retention sequence (14,15), both CD8/⑀ and CD8t were expressed on the cell surface. This allowed separation of transfected COS cells from untransfected cells by immunoselection with antibody-coated magnetic beads.…”
Section: Expression Of a Protein Chimera Containing The Cytoplasmic Tmentioning
confidence: 99%
“…The proline-rich sequence contains the SH3-binding consensus motif XPPXP, and the C-terminal region contains the YXXLXXR endoplasmic reticulum (ER) retention sequence, which partially overlaps the ITAM (14,15). Previous attempts to identify proteins that associate with the cytoplasmic tail of CD3⑀ have shown the specific interaction of a nuclear protein, topoisomerase II␤, and a tyrosine-phosphorylated protein, CAST, with the N-terminal region of the CD3⑀ tail (13,16).…”
mentioning
confidence: 99%